5PSQ-105 Preventing falls in orthogeriatric patients by managing their therapeutic profiles. (24th March 2020) - Oliveira, R; Lobo, T; Marques, L; Pereira, A; Santos, C
Abstract : Background and importance: Elderly people are polymedicated due to their multiple comorbidities. The risks of polypharmacy can be higher than the benefits. Some medicines, labelled 'increasing risk of fall drugs', such as benzodiazepines, antidepressants and antipsychotics, are among the major causes of falls. Thus in order to prevent unnecessary falls and their consequences, there is an urgent need to review patients' therapeutic profiles and to adapt to the real needs of each patient. The orthogeriatric hospital unit was created to provide multidisciplinary care to patients aged >65 years with a hip fracture admitted to hospital. Aim and objectives: To review and optimise the therapeutic profile of patients admitted to the orthogeriatric unit, during hospital admission and follow-up appointments, to prevent the recurrence of falls and fractures. Material and methods: An observational, retrospective, cohort study was conducted in patients aged >65 years admitted to the emergency service with a hip fracture, between the 1 January 2019 and 30 June 2019. These patients were admitted to the orthogeriatric unit during hospitalisation and scheduled for follow-up appointments. Their medication profile was obtained via the digital medical record and the national platform of healthcare. Descriptive statistics was used to summarise the data. Results: A total of 162 patients met the criteria, 75% were women (n=121) and median age was 84 years. The average length of stay was 12.4 days. In 30% (n=48), inappropriate medicines were considered the most likely cause of the fall. During hospitalisation, 316 drugs were suspended and 516 were initiated. Of the 162 patients, 80 already attended follow-up appointments with the general practitioner. From these, 19% (n=15) restarted the inappropriate drugs that were suspended. Conclusion and relevance: It is possible to conclude that the majority of patients had inappropriate drugs in their therapeutic profile. Although only 30% of the patients had medicines as a precipitant factor for the fall, almost every patient had one or more 'increasing risk of fall drugs'. Therefore, these drugs were discontinued to prevent new falls. A considerable percentage of patients restarted the suspended drugs. Consequently, there is a need to find a better strategy to prevent this occurrence. References and/or acknowledgements: No conflict of interest.